2015
DOI: 10.1093/chromsci/bmv055
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Method for Simultaneous Estimation of Metformin and Sitagliptin in Human Plasma by LC–MS-MS and Its Application in a Bioequivalence Study

Abstract: A simple, sensitive, precise and accurate method for simultaneous estimation of metformin and sitagliptin from human plasma was developed and validated. Samples extracted from plasma using acetonitrile were separated on an SCX column and estimated using API 4000 Mass Spectrometer in the positive atmospheric pressure ionization mode (Turboionspray) by following multiple reaction monitoring transitions for both parent and daughter ions. A linear calibration plot was achieved for both the analytes in the concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Several LC-MS/MS method have been reported for the estimation of sitagliptin in biological matrices, such as plasma, urine and hemodialysate. The majority of the reported methods are used in clinical applications (Zeng et al, , 2010Nirogi et al, 2008;Hess et al, 2011;Bonde et al, 2013;Burugula et al, 2013;Reddy et al, 2015;Scherf-Clavel and Högger, 2015) compared with preclinical applications (Yao et al, 2011;Gananadhamu et al, 2012;Patel et al, 2014). Shantikumar et al (2015) reported an LC-QTOF/MS method for the determination of five gliptins (vildagliptin, saxagliptins, sitagliptins, linagliptins and teneligliptin) in clinical application.…”
Section: Hplc Coupled With Ms/ms Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several LC-MS/MS method have been reported for the estimation of sitagliptin in biological matrices, such as plasma, urine and hemodialysate. The majority of the reported methods are used in clinical applications (Zeng et al, , 2010Nirogi et al, 2008;Hess et al, 2011;Bonde et al, 2013;Burugula et al, 2013;Reddy et al, 2015;Scherf-Clavel and Högger, 2015) compared with preclinical applications (Yao et al, 2011;Gananadhamu et al, 2012;Patel et al, 2014). Shantikumar et al (2015) reported an LC-QTOF/MS method for the determination of five gliptins (vildagliptin, saxagliptins, sitagliptins, linagliptins and teneligliptin) in clinical application.…”
Section: Hplc Coupled With Ms/ms Detectionmentioning
confidence: 99%
“…(2008) also used HTLC-MS/MS method to measure sitagliptin levels in human urine and hemodialysate and the method reported by Reddy et al (2015) used 100% acetonitrile (ACN) to get uniform recovery of plasma samples. Patel et al (2014) reported a simple protein precipitation using MeOH which was free from matrix effect and gave high recovery and simple extraction.…”
Section: à80°cmentioning
confidence: 99%
“…It improves the glycemic control primarily through reduction of hepatic gluconeogenesis and by increasing the glucose uptake in peripheral tissues [3,4]. Gliptins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As a result they increase insulin secretion and reduce the glucagon release from pancreas, which down regulate the blood glucose in diabetic patients. The individual members of gliptins are different with respect to their pharmacodynamic and pharmacokinetic properties, whereas they are very similar in anti-hyperglycemic activity and safety [4][5][6]. A recent study has suggested that the gliptins are capable to achieve the target of HbA1c <7% in diabetic patients without causing weight gain or severe hypoglycemia [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is a lipid-soluble form of the Vitamin B-1, prescribed for treating painful nerve conditions by blocking AGEs (Advanced Glycation End products). Literature survey reveals that few HPLC methods have been reported for the estimation of benfotiamine individually and combination with other drugs [25][26][27] The chemical structures of both drugs are shown in Figure 1 and …”
Section: Introductionmentioning
confidence: 99%